EJTIR Referee Acknowledgement 2009 (European Journal of Transport and Infrastructure Research, 2010)
EJTIR wishes to acknowlegde the following referees, whose efforts have made possible the review process for papers submitted to EJTIR in 2008 and 2009 (excluding papers submitted for special issues). Al-Mudhaffar Axhausen Ballis Banerjee le Bouthillier Brons Bruzelius Button Carbone Carney Cheng Chow Cirillo Correljee Dalla Chiara Dickinson Doherty Duivenvoorden Easa Eboli Elvik Fethi Florian Fujii Gillen Giorgi Givoni Gray Greer Grigoroudis Hagenzieker Hartmann Hellendoorn Hilmola Houben Huang Jourquin Kaysi Kikuchi Koetse Kuipers Lawphongpanich van Lint Lord Ludvigsen Maat Mabit Macharis de Martino Mattsson Molenaar Nathanail Ng No Peckan Persaud Polus Reurings Rey Rich van de Riet Rigas Rigo Roorda Rose Snelder Srinivasan Susilo Taale Tampère Tavasszy Thomas Tye Vanelslander Veeneman Verhoef Vovsha Viti van Wee Wiegmans Woodburn Wong Yamamoto Yang Yu Zayed Ziggers Zwahlen